Assessment of provisioning ecosystem services in terrestrial ecosystems of Santa Cruz Province, Argentina. - Rosas, Yamina Micaela; Peri, Pablo Luis; Martinez Pastur, Guillermo José (Springer, 2021)
Provisioning ecosystem services play an important role in the development of regional economies. Traditional managements usually intensify the supply of provisioning services, without consideration of other services (e.g. cultural and supporting) and biodiversity. The objective of this chapter was to characterize main provisioning ecosystem services and potential biodiversity in different terrestrial ecosystems (native forests, shrublands and grasslands) of Santa Cruz Province (Southern Patagonia, Argentina) and to identify potential trade-off areas between provisioning ecosystem services and biodiversity conservation values. We found that non-forested areas exhibited higher supply of provisioning ecosystem services and biodiversity values than forested areas, where potential trade-off areas were located in humid steppes and shrublands. Particularly, in Nothofagus forests landscape, provisioning ecosystem services and biodiversity increased with forest cover, where N. antarctica forests type showed more potential trade-off areas than other Nothofagus forests type, while new potential protected areas were located when different forest types were combined (N. antarctica and N. pumilio). These results can be used by decision-makers to improve management and conservation strategies on private lands.